2003
DOI: 10.1117/12.463915
|View full text |Cite
|
Sign up to set email alerts
|

Influence of chemical composition on the fluorescence lifetimes of crude petroleum oils

Abstract: Fluorescence based methods are increasingly being used for the analysis of crude oils because they offer high speed, low cost, non-contact, and non-destructive testing options. The fluorescence of crude oils is due to the presence of a wide range of cyclic aromatic compounds, with the intensity and temporal behaviour of this fluorescence being directly related to chemical composition. In particular, we have found that the Fluorescence Lifetime (FL) measured at a range of different emission wavelengths is corre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
18
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 16 publications
1
18
0
Order By: Relevance
“…The fact that there are very large numbers of interacting fluorophores produces very complex decay behaviour. In previous work from this laboratory [9][10][11][12][13][14] the intensity averaged lifetime calculated from a multiple discrete lifetime model was used. However, it should be noted that while this model is not an accurate descriptor of the emitting species, it had utility in describing general trends in the photophysics of crude oils.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The fact that there are very large numbers of interacting fluorophores produces very complex decay behaviour. In previous work from this laboratory [9][10][11][12][13][14] the intensity averaged lifetime calculated from a multiple discrete lifetime model was used. However, it should be noted that while this model is not an accurate descriptor of the emitting species, it had utility in describing general trends in the photophysics of crude oils.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies in our laboratory using Time Correlated Single Photon Counting (TCSPC) methods have shown that one can correlate various aspects of oil composition with lifetime changes [9][10][11][12][13][14]. Unfortunately, these studies also showed that accurate quantitative measurements were not possible using intensity averaged lifetimes calculated from TCSPC data.…”
Section: Introductionmentioning
confidence: 96%
“…The physical details and gross chemical composition, and the geographical and source rock information of the oils analysed in this study have been published in detail elsewhere. 35,36 Table 1 outlines the most salient information and Fig. 1 shows a ternary plot of the gross chemical composition of the crude oils used.…”
Section: Methodsmentioning
confidence: 99%
“…27 Fluorescence decay data was collected over the 460 -700 nm wavelength range with a 20 nm step size, and the intensity-averaged fluorescence lifetimes (τ ) were calculated using the same criteria and methods as detailed in previous studies. 21,30,35,36 Results and Discussion:…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation